Carbon sequestered in UK forest products and wood based panels in construction: helping to meet UK's greenhouse gas emission reduction targets. (August 2014) - Robson, D.; Sadler, P.; Newman, G.
<x content-type="archive" xml:space="preserve">Abstract</x> The United Kingdom emitted 628 Mt CO2 equivalent (CO2e) as greenhouse gases in 2008. United Kingdom (UK) policy is to decrease these emissions to 154 Mt by 2050. This paper investigates the role that wood construction products and wood-based panels may play in mitigating these greenhouse gas emissions. In this paper, we have concentrated on production and consumption in 2005: all solid wood products and wood based panels consumed in the UK in 2005 contained almost 16 Mt CO2e. Using established international methodologies and the 'stock change approach' to carbon storage, the net increase in CO2e stored in all UK wood products in 2005 was calculated to be 7·1 Mt CO2e. Applying the newer UNFCCC 'production approach' gave a net increase in CO2e stored in wood based panels and solid wood of 3·4 Mt CO2e in 2005, approximately half of this storage was in wood based panels. The focus of previous UK studies of carbon in construction has been new housing. We estimate that only 10% of CO2e contained in all UK solid wood and wood based panel products consumed went into new housing in 2005. We have modelled the storage of CO2e in solid wood and wood based panels for other construction sectors and used this to model changes in construction methods: if current trends in UK housing construction methods continue and are extended to other construction sectors, there is the potential to increase the annual increment of CO2e stored in wood products in construction from 9 Mt CO2e to 14 Mt CO2e (more than 2% of the total annual UK greenhouse gas emissions).